2014
DOI: 10.1038/bjc.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 inhibits tumour growth and metastasis in colorectal cancer by targeting fascin-1

Abstract: Background:Recent studies have reported miR-145 dysregulated in colorectal cancer (CRC). In this study, miR-145 profiles were compared between CRC and corresponding non-tumour tissues.Methods:The expression levels of miR-145 were analysed in CRC cell lines and tumour tissues by real-time PCR. A luciferase reporter assay confirmed direct targets. The functional effects of miR-145 were examined in transfected CRC cells in vitro and in vivo using established assays.Results:Downregulation of miR-145 was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 26 publications
9
70
0
Order By: Relevance
“…6L,M). Using luciferase assays, we next determined that miR-145 negatively regulated other target genes known to mediate migration, including podxl, fscn1a (fascin actin-bundling protein 1A) and fli1a (Feng et al, 2014;Larsson et al, 2009;Lin et al, 2014) (Fig. 5N).…”
Section: Foxo1a Is Required For Lpm and Ismc Differentiationmentioning
confidence: 99%
“…6L,M). Using luciferase assays, we next determined that miR-145 negatively regulated other target genes known to mediate migration, including podxl, fscn1a (fascin actin-bundling protein 1A) and fli1a (Feng et al, 2014;Larsson et al, 2009;Lin et al, 2014) (Fig. 5N).…”
Section: Foxo1a Is Required For Lpm and Ismc Differentiationmentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…miR-145 induces its functions partially via activating the PAK gene, an important oncogene that promotes cellular migration [20]. PAK overexpression associated significantly with aggressive tumor phenotypes and poor prognosis in CRC patients and therefore it represents a new prognostic factor those patients [10,[21][22][23]. The anti-tumor effect of miR-145 is achieved via targeting insulin receptor substrate-1, the docking protein of IGF1-R, with consequent inhibition of IGF1-R signaling in CRC [24].…”
Section: Discussionmentioning
confidence: 99%